Analyzing the role of the Quadruple Helix in improving MSME management performance - Bernadin D. Ma; Yudi N. Supriadi; Maria A. Wikantari; Nani Ariani; Dahlia Br. Pinem; Pusporini Pusporini (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
This study aims to determine whether the variables of the Quadruple Helix model can enhance the management performance of MSMEs during the new normal era. The study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) for the quantitative design. The research encompasses a sample of 100 MSMEs from Banten Province, Indonesia. Among the four pillars of the Quadruple Helix model-academic, business, local community, and government-business exhibit the most significant influence on management performance, as evidenced by a coefficient value of 0.311. Additionally, government (0.290), academic (0.201), and local community (0.160) display lower coefficients. These findings imply that local community should engage more actively with MSMEs, while the government should enhance its support through policies. Furthermore, MSMEs should seek to gain valuable insights into management practices from academic. The Quadruple Helix model serves as a comprehensive framework that provides government decision-makers with a holistic perspective. Ultimately, this study has the potential to enhance management practices and shed light on strategies for the survival and resilience of MSMEs in a changing economic landscape during the new normal era. It underscores the critical importance of adopting Quadruple Helix thinking for the continued viability of MSMEs.
Keywords: O38; L26; 330; Msmes; Management Performance; Quadruple Helix; Management Practices; Pls-Sem